Pengaruh Problem Based Learning Terhadap Kemampuan Pemecahan Masalah dan Self Efficacy Siswa Kelas VIII SMP Negeri 1 - Destio Tabah Sujarwo (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2020)
This study aims to determine; whether the achievement of problem solving abilities that follow Problem Based Learning is better than the achievement of problem solving abilities that follow direct learning; whether the achievement of self-efficacy that follows Problem Based Learning is better than the achievement of self-efficacy that follows direct learning. This research is a quantitative study with an experimental method using the Post-Test Only Control Design method. The population in this study were all students of class VIII SMP Negeri 1 Patikraja. Sampling using cluster random sampling by taking two classes, namely class VIII F using Problem Based Learning and class VIII D using direct learning. Data analysis using Independent Sample t-Test for one-sided test right on the post test and questionnaire with α = 0.05. Obtained a significant value of problem solving ability of 0.031 and self-efficacy of 0.038. Both significant values are less than 0.05. The conclusion in this study is Problem Based Learning affect the ability of problem solving and self-efficacy of students.